Democracy as experimentalism and experimentalism as antidogmatism: John Dewey and the theory of education today - Saharrea, Juan Manuel (2022)
Our purpose in this paper is twofold: on one hand, to reconstruct Dewey’s conception of experimentalism, mainly through his pedagogical writings; and, on the other hand, to show the relevance of this reconstruction to current reassessments of Dewey’s political thought. The grounds for our perspective have a double character, too. First, we reconstruct the links between experimentalism and education on the basis of the first edition of How We Think (1910, MW 6); perhaps one of Dewey’s most noteworthy pedagogical texts. Secondly, we critically address three different reassessments of Dewey’s experimentalism in contemporary political thought, namely: (1) Pappas’s defense of Dewey’s substantive idea of democracy; (2) Forstenzer’s proposal of Deweyan experimentalism as an appropriate methodology for political philosophy; and (3) Anderson’s vindication of Deweyan experimental democracy in the context of social epistemology. We posit that in HWT Dewey places experimentalism as a kind of antidote against dogmatism and unreflective ways of reasoning. As a consequence, he links experimentalism with anti-dogmatism placing a special role in schooling for at least two reasons: (1) it is during the schooling phase that children are still sensitive to the development of certain habits; (2) dogmatism seems inevitable in any society but the educational phase is a key instance to try to avoid it. Neither (1) nor (2) are present in contemporary reassessments of Deweyan experimentalism.